Political bias in court? Lay judges and asylum appeals - Linna Martén (Uppsala University, Department of Economics, 2015)
Several countries practice a system where laymen, who lack legal education, participate in the judicial decision making. Yet, little is known about their potential influence on the court rulings. In Sweden lay judges (namndeman) are affiliated with the political parties and appointed in proportion to political party representation in the last local elections. This paper investigates the influence of their partisan belonging when ruling in asylum appeals in the Migration Courts, where laymen are e ectively randomly assigned to cases. The results show that the approval rate is affected by the policy position of the laymen's political parties. In particular, asylum appeals are more likely to be rejected when laymen from the anti-immigrant party the Swedish Democrats participate, and less likely to be rejected when laymen from the Left Party, the Christian Democrats or the Green Party participate. This indicates that asylum seekers do not receive an impartial trial, and raises concerns that laymen in the courts can compromise the legal security in general.
urn:nbn:se:uu:diva-252356
Keywords: D72; D79; K10; K37; K40; 330; Political attitudes; Decision making; Court; Immigration; Legal system